Characteristics Condition and Environmental Quality of Using Tribe Settlements in Kemiren Village - Abu Sufyan; Tri Anggraini Prajnawrdhi; Ni Ketut Agusintadewi (Journal of Architecture & Environment, 2020)
As a built environment, Kemiren Village’s development as traditional tourist village, has brought benefits that are very impactful to the community. However, the economic growth, apparently were not followed by improvement of settlement’ characteristics quality and environmental quality, this is due to the diminishing of important elements which should provide high significance in cultural value. The condition has been significantly damaged, and the number continues to decrease. In addition, many settlement’s environmental quality condition needed improvement. Control to maintain the characteristics from threat of change needs further review. Thus, it is necessary to re-identify settlement’s characteristics from the influence of cultural significance and environmental quality, of which result can be utilized to develop Using tribe’s preservation direction in Kemiren Village. Which could bring benefit of saving the existence of traditional settlements from losing their characteristic value, as well as to improve the residential’s environment quality as a settlement area. Research conducted by rationalistic-qualitative, descriptive and exploratory methods. The technique for data collection is through field observation, interviews and documentation. Furthermore, the data obtained would be mapped into table, covering environment physical condition, characteristics, cultural significance, and environmental quality. Based on evaluation analysis, the settlements cultural significance value reaches an average of 60% with variables as aesthetics, rarity, and extraordinariness, are elements with significant score, given the existence of ancient Kemiren House. Whereby the environmental quality value which falls below average of 40%, posed threat to physical form, which can visually reduce aesthetic value and quality of traditional residence, as a comfortable place.